Electronic structure and optical properties of conjugated molecules : SAC-CI study - Ehara, Masahiro (2013)
Electronic structure and optical properties of some organic conjugated molecules, that is the oligomers for organic-light emitting diodes (OLED), chelating hetero-atomic conjugated ligands, and UVB blocking molecules, have been investigated by the SAC-CI method. The absorption and emission spectra of these molecules were reproduced accurately. For OLED molecules, chain length dependence of the excitation and emission energies was evaluated for poly para-phenylene vinylene and poly para-phenylene. Thermal effect on the electronic spectra of fluorene-thiophene and its derivatives was examined with taking accounts the Boltzmann distribution. The photophysical properties of the chelating hetero-atomic molecules including pyridine-, benxazole-, and benzothiazole derivatives which are useful for electroluminescent metal complex were systematically calculated. The UVB blocking function of the methoxy substituted cinnamates was investigated with regard to the substitution position. The excited-state geometry relaxation of these molecules was interpreted based on the electrostatic force theory. The present work provides a useful basis for the theoretical design predicting the optical properties of the photo-functional molecules.